Mutations Determining Mitomycin Resistance in Bacillus subtilis - Iyer, V. N. (1966)
Iyer, V. N. (Microbiology Research Institute, Canada Department of Agriculture, Ottawa, Canada). Mutations determining mitomycin resistance in Bacillus subtilis. J. Bacteriol. 92:1663–1669. 1966.—The pattern of development of genetic resistance in Bacillus subtilis to mitomycin C was studied, and spontaneous single and multistep mutants were obtained. The transmission and expression of these mutations in sensitive strains proved possible by means of genetic transformation. The mutations were genetically studied in relation to a chromosomal mutation, mac-1, which confers resistance to the macrolide antibiotic erythromycin and which has been previously localized in the early-replicating segment of the B. subtilis chromosome. The results indicate that all of three primary mutations studied in this manner, as well as a secondary and tertiary mutation derived from one of the primary mutations, are clustered in this early-replicating segment. It appears that the secondary and tertiary mutations enhance the resistance conferred by the primary mutation, apparently without themselves conferring any resistance.